2021
DOI: 10.3390/agriculture11040303
|View full text |Cite
|
Sign up to set email alerts
|

A Biotreatment Effect on Dynamics of Cattle Manure Composition and Reduction of Ammonia Emissions from Agriculture

Abstract: Increasing control of localized air pollution caused by ammonia is identified, including limiting the maximum emissions from agriculture. In EU countries, the agricultural sector is the source of above 94% of the total anthropogenic emissions of ammonia, of which manure removal systems account for 56%. In view of the reason for the agricultural waste management by formation and propagation of ammonia gas—the bacterial and enzymatic degradation of organic components in excrement—it is important to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…During heat, it is recommended to cool the air in the barn or use biological manure treatment that reduces ammonia emissions by more than 30%. The maximum effect of the biological treatment of manure on ammonia emissions occurs after 28-35 days [39].…”
Section: Discussionmentioning
confidence: 99%
“…During heat, it is recommended to cool the air in the barn or use biological manure treatment that reduces ammonia emissions by more than 30%. The maximum effect of the biological treatment of manure on ammonia emissions occurs after 28-35 days [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, modeling of the operation of the barn recuperative ventilation system with air flow adsorption equipment in livestock farms showed that the required microclimate in the barn is ensured [25]. The control group received cooling sessions according to a pre-determined schedule, a method commonly used on farms; and an experimental group that received a sensor-based (SB) cooling mode.…”
Section: Discussionmentioning
confidence: 99%
“…The field of attenuation of biological processes of nitrification and denitrification, the course of which is accompanied by an increase in temperature (Figure 5) and a change in pH (Figure 6), the active phase of ammonia emission begins, in our case after 56 days. Usually this phase is accompanied by the release of an unpleasant odor and negative impact on the atmospheric air [1][2][3]. However, the introduction of citrogypsum into the compost makes it possible to bind the released ammonia according to the Formula (1), which explains the increase in the nitrogen content in the compost (Figure 7b).…”
Section: Study Of the Effect Of Cg On Ammonia Volatilizationmentioning
confidence: 99%
“…Animal waste is a significant factor that negatively affects the environment. This, in particular, is expressed in the formation of greenhouse gases, an unpleasant odor, the spread of pathogenic microorganisms, etc., which actually worsens the ecological situation [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation